Implementación de anestesia regional guiada por ultrasonido en el Hospital General Docente de Calderón - Calero Robles, Manolo D (2018)
Technological advances in the field of Anesthesiology allow the use of ultrasound as diagnostic and therapeutic support in patients who require surgical intervention. The objectives of using diagnostic support methods include improving the safety and quality of both anesthetic and analgesic care. To incorporate imaging procedures into the daily activities of the anesthesiologist, it is necessary to include new knowledge, skills and abilities in the field of anatomy and basic aspects of ultrasound, to adapt to the use of a high frequency linear transducer and follow real-time images that facilitate the administration of the local anesthetic. The interest of the authors is to share two years of experience in the use of ultrasound for various types of regional blockages